Anisotropic metal nanoparticles for surface enhanced Raman scattering. (27th April 2017) - Reguera, Javier; Langer, Judith; Jiménez de Aberasturi, Dorleta; Liz-Marzán, Luis M.
Abstract : Anisotropy in plasmonic metal nanoparticles plays a major role in the enhancement of the Raman scattering of adsorbed molecules. Abstract : The optimization of the enhancement of Raman scattering by plasmonic effects is largely determined by the properties of the enhancing substrates. The main parameters behind this effect are related to the morphology of plasmonic nanoparticles and their relative distribution within the substrate. We focus this tutorial review on the effects of nanoparticle morphology, for the particular case of anisotropic metal nanoparticles. Anisotropy in silver and gold nanoparticles offers the possibility to tailor their plasmonic properties and intrinsic electromagnetic "hotspots". We describe the effect of varying particle size and shape on the SERS signal, focusing on the most common anisotropic morphologies used for SERS. Especial emphasis is made on existing comparative studies that shed light on the effect of nanoparticle anisotropy on their enhancement capabilities. We aim at providing a general perspective toward understanding the general key factors and highlighting the difficulty in quantitatively determining SERS performance.